Growth, productivity, physical and economic optima and yield gaps estimation in wheat (Triticum aestivum L.) through site specific nutrient management approaches under inner-Terai region of Chitwan, Nepal - Marasini, Sudeep; Amgain, Lal Prasad (Journal of Agriculture and Natural Resources, 2021)
An on-farm field experiment was accomplished during the winter season of 2018/19 under inner Terai region at Khairahani, Chitwan for evaluating the influence of various site specific nutrient management approaches on growth, yield, optimum fertilizer dose and yield gaps of wheat (Triticum aestivum, L.). The experiment was laid out in Randomized Complete Block Design (RCBD) in three replications with different eight nutrient management practices: T1- farmers fertilization practice (FFP) (52:33:18 kg NPKha-1), T2 - Blanket recommendation (BR) (100:50:25 kg NPK ha-1), T3 - SSNM-NE (110:47:46 kg NPK ha-1),T4 - LCC-N+NE-P&K, T5 - NE-N + farmers -P&K, T6 - LCC- N + farmers–P&K, T7 - Nitrogen Omission Plot (NOPT) + NE- P&K, and T8 - NARC recommendation (120:60:40 kg NPK ha-1). The result findings indicated that the NARC recommendation was comparatively superior over other treatments in terms of plant height, dry matter accumulation, crop growth rate and yield, but the profitability (B:C ratio) was found higher in SSNM-Nutrient Expert recommendation. The physical and economic optimum level of fertilizer for wheat obtained was 135:47.66:43.94 kg NPK ha-1 and 130: 47.86:43.61 kg NPK ha-1, respectively. The yield gaps between farmers practice and SSNM-Nutrient Expert was found to be 110% and 41%, respectively over potential yield of wheat. Thus, it could be suggested that there is great potential to improve the yield of wheat through the NARC recommendation and the SSNM- Nutrient Expert model to raise sustained productivity and income of wheat farmers in inner-Terai region of Nepal.